2008
DOI: 10.1016/j.matdes.2006.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of polypropylene composites reinforced with oil palm empty fruit bunch fiber and oil palm derived cellulose

Abstract: In recent years, the race for producing biodegradable products has increase tremendously. Different approaches have been attempted to use biomass as natural biopolymer for production of biodegradable plastics. In this work, cellulose was derived from oil palm empty fruit bunch fiber (EFBF) by standard ASTM D1104 method. The cellulose and EFB fibers were blended in different ratios up to 50-wt.% with polypropylene (PP) using Brabender twin-screw compounder. Effects of cellulose and EFB fibers on the mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(93 citation statements)
references
References 27 publications
5
66
1
6
Order By: Relevance
“…These findings suggest that OPEFB with nano size proved to improve a mechanical property in terms of the impact strength of the biocomposites compared with those with long fibers. These results are in agreement with those obtained by Khalid et al (2008). The impact strength of the biocomposites is strongly influenced by the nature of the fiber, polymer, fiber-matrix interfacial bonding, and testing conditions (Joseph et al 2003).…”
Section: Impact Propertiessupporting
confidence: 91%
“…These findings suggest that OPEFB with nano size proved to improve a mechanical property in terms of the impact strength of the biocomposites compared with those with long fibers. These results are in agreement with those obtained by Khalid et al (2008). The impact strength of the biocomposites is strongly influenced by the nature of the fiber, polymer, fiber-matrix interfacial bonding, and testing conditions (Joseph et al 2003).…”
Section: Impact Propertiessupporting
confidence: 91%
“…The results obtained in the current paper showed similarity in trend compared to those available in the open literature [1], [2], [4]. Experimental measurement on the composites depict a rather wide range of error bars compared to pure epoxy, these deviations arise due to the nature of the palm fibres where the milling process could not effectively separate the EFB fibres into individual strand and a large proportion are still attached together in a bunch.…”
Section: Discussionsupporting
confidence: 78%
“…The overall increasing trend could be attributed to the higher stiffness of the composite due to improved fibre reinforcement with higher interfacial bonding between matrix and fibres. Similar results were obtained by Khalid et al on EFB palm fibre/polypropylene (PP) composite, where the authors observed an increase of filler content caused a steady increase in flexural modulus [2].…”
Section: International Journal Of Materials Mechanics and Manufactursupporting
confidence: 87%
See 1 more Smart Citation
“…This gives poor interfacial interaction between PP and PKS thus, lead to the poor strength of the composite. Poor dispersion of PKS inside PP matrix also contributed to the strength deterioration of the composites [15] . Nevertheless, PKS reinforced PP biocomposites appeared to have higher tensile strength with the addition of PP-g-MAH and PP-POSS.…”
Section: Mechanical Testmentioning
confidence: 99%